Financial Literacy Education And Retirement Planning In Malaysia - Selvadurai, Visyalini; Kenayathulla, Husaina Banu; Siraj, Saedah (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2018)
Lack of education in financial literacy would lead to fallacious retirement planning decisions among elderly people. Many elderly people are facing dilemma of not having sufficient money to maintain their living upon retirement and this problem is becoming worse over time. Thus, this qualitative study explores the financial literacy education of elderly people and the influence on retirement planning in Malaysia. Data for probing the influence of financial literacy education on financial retirement planning of elderly people in Malaysia were collected using semi-structured interview questions and document analysis. Data were collected from 10 elderly people with financial education background and have experience in dealing with financial planning for retirement from Klang Valley, Malaysia. Purposeful sampling technique was used to collect data and thematic analysis was used to interpret the data collected in this study. The results of this study indicated that financial literacy education along with demographic factors and financial attitude factors play a crucial role in financial retirement planning before retirement. The results further indicate that psychological factors like monetary goal-setting, early financial exposure and financial awareness affect elderly people in enhancing financial literacy education, which eventually influence financial retirement planning. In order to improve on the financial planning for retirement, policy makers and government need to implement financial literacy education policy to aid elderly people in financial planning and retire with financial freedom.